-1d=4d

Simple and best practice solution for -1d=4d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1d=4d equation:


Simplifying
-1d = 4d

Solving
-1d = 4d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-4d' to each side of the equation.
-1d + -4d = 4d + -4d

Combine like terms: -1d + -4d = -5d
-5d = 4d + -4d

Combine like terms: 4d + -4d = 0
-5d = 0

Divide each side by '-5'.
d = 0

Simplifying
d = 0

See similar equations:

| y/8-2=6 | | 2x-3y=125 | | x^2+8xy+16y^3=0 | | 12/5÷60 | | -18=-7w+12 | | -1/1/4= | | 8y+4+4y+8=15y-8 | | 81x^2-12=0 | | 0.27y=-0.81 | | -25=2+3x | | 0.27y=-081 | | -8v+6v=-10-7v | | 3a(6+2)= | | (8x+4)+(3x+4)=140 | | 20b=6 | | 7y+13=9y-5 | | 2(3y-12)=4y+8 | | 4n^3+5n^2+n+1=0 | | n-29=-33 | | X+12=-6y-2 | | 7/8p-4/1=10 | | c^2-11cd+24d^2= | | 5x/x-1=30/9 | | 5x+6-3x=14 | | 27^-2/3)•27^-(1/3) | | 3(x+3)=4(x+2) | | 3a+4b-2a-b=0 | | .5(x-4)=-1.50+6 | | r^2-7x-18=0 | | -21h=b | | 2v=-20 | | 8/2.5=d/.5 |

Equations solver categories